Review Of Compensation , Commitment And Work Motivation Their Influence On Employee Performance PT. Pegadaian (Persero ) VI Makassar - Romansyah Sahabuddin; Taslim Dangnga (Seminar Nasional LP2M UNM, 2021)
Abstrak. This research was aimed at examining the correlation among compensation, commitment and motivation toward employee performance at PT Pegadaian (Persero) VI Makassar region. The research problems were; 1) How does compensation affect employee performance? 2) How does commitment affect employee performance? 3) How does motivation affect employee performance? 4) How do compensation, commitment and motivation affect employee performance?. The analysis tools used in this research was multiple regression through aplication system, SPSS. The respondent of the research was employee of PT. Pegadaian (Persero) Wilayah VI Makassar with the total number of employee was 63. The result showed whether partial and simultaneous compensation , commitment and work motivation have a positive influence significantly to employee performance. Kata Kunci: Compensation, Commitment, Work Motivation, Individual Performance